Sosialisasi Penguatan Ideologi Pancasila Bagi Peserta Didik SMIP Universitas Simalungun - Ulung Napitu; Corry; Tutyariani Nasution; Rosmeri Saragih; Desmi Triyanti Purba (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
This community service aims to provide understanding and re-grounding of the importance of the position of state ideology in the life of the nation and state in Indonesia, because Pancasila for the Indonesian people works as a philosophy of life and a view of life that is excavated from the crystallization of the socio-cultural values of the Indonesian nation. The importance of re-earthing the values of Pancasila in the lives of all levels of society because post-reformation until now has been found to be an indication of the strengthening of radicalism, intolerance and moral degradation in the lives of all levels of Indonesian society. If this condition continues to develop, it is feared that it will encourage disintegration of the nation. Moral degradation and radicalism have not only hit many people but have also entered the world of education. Therefore, it is important to implement the earthing of Pancasila to all levels of society in general and students in particular in all educational units. To socialize and ground the material on the ideology of the Pancasila state to students, students use the lecture and question and answer method which lasts for 120 minutes. With the socialization and grounding of Pancasila for junior high school students, the tourism industry of the USI Foundation, it is hoped that early on, students will be spared from various movements of radicalism, intolerance and moral decadence that are currently developing in the younger generation and students in particular. To socialize and ground the material on the ideology of the Pancasila state to students, students use the lecture and question and answer method which lasts for 120 minutes.